Exploring the synergistic effects of amoxicillin and methylene blue on unsaturated lipid structures: A study of Langmuir monolayers and giant unilamellar vesicles - Maximino, Mateus D. [UNESP]; Kavazoi, Henry S. [UNESP]; Katata, Victoria M. [UNESP]; Alessio, Priscila [UNESP] (Elsevier, 2024)
The potentially toxic effects of emerging pollutant mixtures often deviate from the individual compound effects, presenting additive, synergistic, or agonistic interactions. This study delves into the complex world of emerging pollutants' mixtures, with a particular focus on their potential impact on unsaturated lipid DOPC (1,2-dioleoyl-sn-glycerol-3-phosphocholine) structured as both monolayers and bilayers, which are valuable tools for mimicking cell membranes. Specifically, we examine the effects of two common types of pollutants: antibiotics (amoxicillin) and dyes (methylene blue). Utilizing Langmuir monolayers, our research reveals a synergistic effect within the pollutant mixture, as evidenced by pressure-area isotherms and polarization-modulated infrared reflection absorption spectroscopy. We identify the specific chemical interactions contributing to this synergistic effect. Furthermore, through contrast phase microscopy experiments on giant unilamellar vesicles (bilayer system), we find that the individual pollutants and the mixture exhibit similar molecular effects on the bilayer, revealing that the molecular size is a key factor in the bilayer-mixture of pollutant interaction. This highlights the importance of considering molecular size in the interactions with bilayer systems. In summary, our research dissects the critical factors of chemical interactions and molecular size concerning the effects of pollutants on DOPC, serving as simplified models of cell membranes. This study underscores the significance of comprehending the molecular effects of emerging pollutants on human health and the development of models for exploring their intricate interactions with cell membranes.
Keywords: Amoxicillin; Giant unilamellar vesicles; Langmuir films; Membrane models; Methylene blue; Mixture of pollutants